Development and initial validation of the Spanish form of the adjustment scales for preschool intervention (ASPI). (February 2021) - Bulotsky-Shearer, Rebecca J.; McDermott, Paul A.; Lopez, Michael; Gort, Mileidis; Bouza, Johayra; Fernandez, Veronica; Bichay-Awadalla, Krystal
Abstract: The purpose of the study was to develop and validate a Spanish language form of the Adjustment Scales for Preschool Intervention (ASPI) for use by early childhood teachers. A multi-step, mixed method adaptation and translation process of the English form was used to increase the cultural relevance, linguistic comparability, and metric equivalence of the measure in its Spanish language form. Exploratory and confirmatory factor analyses in a diverse sample of preschool children from low-income families ( N  = 4077) revealed two higher order behavioral dimensions of Overactivity and Underactivity. ASPI dimension scores across Spanish and English language forms were horizontally equated through IRT. Criterion-related validity using multilevel models was established through concurrent associations with social, emotional, behavioral, and academic readiness skills. Policy and practice applications, and future directions for the use of scale scores are discussed.